Mapping policies and programmes: the use of GIS to communicate spatial relationships in England. (November 2015) - Wong, Cecilia; Baker, Mark; Webb, Brian; Hincks, Stephen; Schulze-Baing, Andreas
It has long been acknowledged that there is a gap between the advancement of GIS in the research field and its application in planning practice. This paper demonstrates the potential for employing simple GIS mapping overlays as a way of communicating complex planning issues in a 'language' that is easily understandable and effective at stimulating policy debate, critical thinking, and learning. The analysis focuses on capturing the synergies and conflicts in two key planning challenges in England, progrowth and housing delivery agendas. In a political context where spatial evidence-based policy making has been eroded in recent years, the analysis demonstrates the need for policy makers to 'think spatially, act spatially' when developing different policies and programmes. The paper concludes that only by making spatial relationships of policies and programmes explicit in a manner that is easily understood by a range of actors, can different spatial scenarios and metaphors of future opportunities and challenges be developed to inform long-range development and planning.